1985
DOI: 10.1038/316069a0
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of human T-lymphotropic virus type III by sera of AIDS and AIDS-risk patients

Abstract: Human T-lymphotropic virus type III (LAV, HTLV-III) is aetiologically linked to acquired immune deficiency syndrome (AIDS) and persistent general lymphadenopathy (PGL). Specific radioimmunoassays (RIA), enzyme-linked assays, immunofluorescence assays (IFA) and immunoblotting techniques are being used widely to detect serum antibodies to HTLV-III in infected patients and in those at risk of infection. However, these assays do not functionally identify those antibodies that neutralize the infectivity of the viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
162
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 431 publications
(164 citation statements)
references
References 30 publications
2
162
0
Order By: Relevance
“…HIV+ sera exert group-specific neutralizing activities (22)(23)(24). Recent reports (25,26) also demonstrated that the group-specific neutralizing activities disappeared after absorption ofthe sera on gpl60.…”
Section: Resultsmentioning
confidence: 99%
“…HIV+ sera exert group-specific neutralizing activities (22)(23)(24). Recent reports (25,26) also demonstrated that the group-specific neutralizing activities disappeared after absorption ofthe sera on gpl60.…”
Section: Resultsmentioning
confidence: 99%
“…In this reaction, specific antibodies bind to HIV antigens on the surface of infected cells, which are then killed by Fc receptor-positive effector cells [13]. HIV-specific antibodies from infected individuals have also been found to neutralize viral infectivity in vitro [14,15]. Although the in vivo role is not fully understood, it is likely that neutralizing antibodies are most important in the anti-viral defence.…”
Section: Introductionmentioning
confidence: 99%
“…Robert-Guroff et al 1985, Weiss et al 1985. In the course of the last three years, however, the high protection obtained in monkeys infused with anti-HIV-1 monoclonal antibodies has increased interest in HIV-1 neutralization (Baba et al 2000, Mascola et al 2000, Nishimura et al 2002, Ferrantelli et al 2004.…”
mentioning
confidence: 99%